Application of Semi Fowler Position to Inaffectiveness of Breathing Patterns in Congestive Heart Failure (Chf) Patients - Iif Taufiq El Haque; Asep Gunawan; Sari Puspayanti (LPPM STIKes Muhammadiyah Ciamis, 2021)
Objective: This study aims to present care with semi-Fowler's intervention as an effort to overcome shortness of breath in congestive heart failure patients with ineffective breathing patterns in the Kenanga Room, BLUD RSU Kota Banjar. Method: Descriptive analysis plus a case study technique make up the research design. Adult patients with congestive heart failure (CHF) and dysfunctional breathing patterns were the study's subjects. Interviews, observation, physical examinations, and documentation studies are a few of the methods of data collection. Result: The results of the case study at the assessment stage found that the client complained of shortness of breath. The intervention and implementation used to reduce shortness of breath is by giving the semi-Fowler's position by positioning the patient half-sitting or 45 degrees, while the shortness lasts. After the intervention, the client's breathing frequency decreased from 28 x/minute to 22 x/minute, while the subjective data from the anamnesis showed that the client's shortness of breath was reduced. Conclusion: The conclusion of nursing care in patients with congestive heart failure (CHF) with shortness of breath is well resolved. Intervention in the semi-fowler's position is effective in reducing respiratory frequency.